2023
DOI: 10.1097/sap.0000000000003458
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intraoperative Hypothermia on Autologous Breast Reconstruction

Abstract: Objective: Studies have identified perioperative hypothermia as a risk factor for impaired wound healing, increased hospital length of stay, and surgical site infection. This study examines the effect of intraoperative hypothermia on postoperative outcomes in autologous microvascular free flap breast reconstruction. Methods: This was a retrospective review of 55 patients who experienced intraoperative hypothermia, defined as less than 35.0°C core body temperature and 99 normothermic patients who underwent auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
(97 reference statements)
0
1
0
Order By: Relevance
“…The core temperature of normal people is 36.5–37.5 °C [ 2 ]. Intraoperative hypothermia is defined as a core body temperature below 36 °C during the period of anesthesia and surgery, a condition that can arise due to a multitude of factors [ 3 ]. It is reported that the incidence of hypothermia during operation is 40.13 %–75.06 % [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The core temperature of normal people is 36.5–37.5 °C [ 2 ]. Intraoperative hypothermia is defined as a core body temperature below 36 °C during the period of anesthesia and surgery, a condition that can arise due to a multitude of factors [ 3 ]. It is reported that the incidence of hypothermia during operation is 40.13 %–75.06 % [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%